Electricity Usage Monitoring Based On Internet of Things - Ahmad, Mohd Ridzuan; Hashim, Hishamuddin (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Electricity monitoring systems have long been used in industrial scenarios such as process scheduling and distribution. This monitoring system needs to be developed for domestic use such as in homes and shops. In recent times, the electricity demand has increased in households with the use of different appliances. The advent of technologies such as the Internet of Things (IoT) has made real-time data acquisition and analysis possible. This project is designed to control and monitor household electricity consumption via smartphones using the ESP8266 Wi-Fi module as a communication protocol and the Blynk application as a private server. The used wifi module provides notification through the Blynk application. The system uses an Arduino Mega2560 microcontroller to control all devices in this project. For monitoring the energy usage, a current sensor type Split Core Current Transformer (SCT013) was used. From the experimental results, it is confirmed that the system is capable of monitoring the whole house’s electrical usage easily. With this system in place, end-users are provided with proper awareness and able to plan their home’s electrical consumption pattern effectively.